2019
DOI: 10.1039/c8py01355a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multifunctional miktoarm star polymers via an RGD peptide-based RAFT agent

Abstract: A “grafting from” approach for facile access of multifunctional miktoarm star polymers containing peptide arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…A variety of monomers can be easily polymerized with controllable molecular weights (MWs) and low polydispersity (PDI) [15,16,17,18,19,20,21]. Among LPs, reversible-deactivation radical polymerizations (RDRPs) are one of widely used methods, mainly covering atom transfer radical polymerization (ATRP) [22,23,24,25] and derivatives [26,27,28,29], reversible addition–fragmentation chain transfer (RAFT) polymerization [30,31,32], nitroxide-mediated radical polymerization (NMP) [33], ring-opening (metathesis) polymerization (RO(M)P) [34,35], and unique chain-growth condensation polymerization (CGCP) [15,19,36]. Furthermore, several recent modelling studies demonstrated the emergence of joint collaboration between chemists and engineers in the field of LP.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of monomers can be easily polymerized with controllable molecular weights (MWs) and low polydispersity (PDI) [15,16,17,18,19,20,21]. Among LPs, reversible-deactivation radical polymerizations (RDRPs) are one of widely used methods, mainly covering atom transfer radical polymerization (ATRP) [22,23,24,25] and derivatives [26,27,28,29], reversible addition–fragmentation chain transfer (RAFT) polymerization [30,31,32], nitroxide-mediated radical polymerization (NMP) [33], ring-opening (metathesis) polymerization (RO(M)P) [34,35], and unique chain-growth condensation polymerization (CGCP) [15,19,36]. Furthermore, several recent modelling studies demonstrated the emergence of joint collaboration between chemists and engineers in the field of LP.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in responsive behavior (pH 7 to pH 10) can be ascribed to the specific interactions between the carboxylic acid group and Ca 2+ . 35 According to our hypothesis (Scheme 2), another possible reason is that as the end-groups were gradually ionized, the electrostatic repulsion increased leaded to the enlarging chain spacing with a decrease in the rigid region and an increase in the amount of flexible chains (Scheme 2b), finally caused an increase in UCST. In other words, carboxylic end-groups could also affect UCST by changing the chain conformation.…”
Section: -38mentioning
confidence: 85%
“…Peptide-functionalized macroinitiators have been designed to prepare linear and star polymers bearing a peptide at the extremity of the polymer chain. [232] Different approaches and polymerization techniques have been explored including NMP, [233] ATRP, [234] and RAFT polymerization [235] from a peptide grafted on the resin, peptide-bearing initiator or chain transfer agent used under ATRP [236] and RAFT [237][238][239] polymerization conditions, ring-opening polymerization of N-carboxyanhydrides from peptide-PEG macroinitiator. [240] The use of peptide-containing macromonomers afford polymers bearing peptides on the side chains of the polymer backbone.…”
Section: Peptide Conjugation On Hbpsmentioning
confidence: 99%